Great Muslim leaders : lessons for education - Brooks, Melanie C., 1972-; Ezzani, Miriam D. (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"Great Muslim Leaders presents Islamic-informed alternatives to Eurocentric Christian understandings of education and educational leadership. It does so by interrupting and displacing the West's centuries long dismissive stance and monolithic gaze on Islam by showcasing outstanding diverse Muslim leaders across space and time. Each chapter focuses on a single leader, and includes a biographical sketch; a discussion of their context and activities as a leader; key lessons readers can learn from their leadership, and recommendations that are relevant for teachers and educational leaders. This collection of Muslim leaders, chosen by Muslim scholars, brings to education discourse the breadth of Islamic intellectual history, giving the book a global appeal and facilitating a sharing of innovative and classic ideas across cultures, faith traditions, and national boundaries. Great Muslim Leaders introduces to readers Muslim intellectuals, spiritual leaders, philosophers, poets, artists, activists, scientists, celebrities, politicians, educators, film makers, historical figures, theorists, and academics whose lives have positively shaped their community, society, and the world. Their lived experiences are underpinned by deep spirituality and faith, revealing the significance and import religious belief has on moral and ethical action. The book concludes with seven lessons that cut across the chapters that encapsulate the immense value Islamic spirituality and faith bring to education and leadership"--